Study of The Violin Book for The Development of Beginner Level Violin Teaching Materials Based on National Song - Urfan Saniylabdhawega Ridhwan; Rita Milyartini; Diah Latifah (Gondang: Jurnal Seni dan Budaya, 2023)
The violin is proven to be able to build the positive character of a nation. Venezuela's experience with its program, El Sistema, where the violin instrument is learned by the wider community, has had a positive impact in terms of social and economic aspects, including a sense of empathy, cooperation, self-confidence and can help increase awareness of national identity. In Indonesia, the violin is known as a western classical musical instrument. This assumption is supported by the rise of violin course institutions that use eurocentric teaching materials. Learning from Venezuela's experience, an effort is needed to develop violin teaching materials that offer material related to Indonesian National songs, as an effort to build national character. As a first step, a review of beginner level violin books with high credibility will be carried out. The purpose of this study is to determine the characteristics of beginner level violin teaching materials. The research method used is analytical descriptive. This process is expected to produce the basics that need to be considered in the process of developing teaching materials, especially teaching materials for violin musical instruments. The researcher hopes to be able to inspire researchers who are developing music teaching materials through a content analysis process carried out by researchers to produce teaching materials with international standards.